The shattered skies - Birmingham, John, 1964- (The cruel stars trilogy, 2022)
"Humanity's last remaining heroes must rebuild and protect civilization after a long dormant enemy shattered their once-peaceful empire in this thrilling sequel to The Cruel Stars. The Sturm, a group of "species purists" intent on destroying any human with genetic or cybernetic enhancements, returned from the far reaches of Dark Space to wage a war against humanity. Though their victory seemed inevitable, a small group of reluctant heroes managed to beat back the invading force. Now left with the remains of a crippled civilization, they must work together to rebuild--and to stand guard, in case those weren't the only enemies hiding in the dark.."--